Visible light-promoted, photocatalyst-free C(sp(2))-H bond functionalization of indolizines via EDA complexes - Mane, Kishor D.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2022)
The catalyst and additive-free, photo-driven cross dehydrogenative coupling (CDC) reaction initiated by electron donor-acceptor (EDA) complexes between electron rich indolizines and electron poor quinones has been demonstrated. This green transformation reveals the advantages of operational simplicity, mild reaction conditions and good functional group tolerances.
Keywords: Blue LED; CDC; EDA; Indolizine; Quinone